الدور الاصلاحي لجمعية العلماء المسلمين الجزائريين - جريدة السنة النبوية المحمدية -دراسة تحليلية - غربي, حمزة; سعود, ابراهيم (University of Eloued جامعة الوادي, 2020)
" يتناول هذا البحث أحد أهم مخرجات الحركة الوطنية الجزائرية, ألا وهو جمعية العلماء المسلمين الجزائريين, ودورها الإصلاحي في مرحلة مهمة من تاريخ الجزائر, ساد فيها الجهل والانحراف وانعدم فيها التعليم بفعل السياسات التي كان يمارسها الاستعمار الفرنسي, حيث حاولت الجمعية التي تأسست في هذه الظروف أن تساهم في إصلاح واقع الجزائريين المزري, ولقد كان لكتابات رجالاتها وأعمالها الأثر الكبير من خلال الكتابة في الصحف والجرائد. حيث يحاول البحث تسليط الضوء على جريدة السنة النبوية والتي تعتبر أول جريدة تصدرها الجمعية, وذلك بدراسة موضوعاتها دراسة تحليلية من خلال الوقوف والتركيز على الدور الإصلاحي الذي قامت به الجمعية, والذي تركز أساسا في: الإصلاح الديني والإصلاح السياسي, بالإضافة إلى الإصلاح " The core of this study deals with one of the most important outcomes of the Algerian national movement, which is the Algerian Muslim Scholars Association and its reformative role during a crucial episode of the Algerian modern history. Due to the deliberate colonial policies followed by the French colonisation, that period was infamous of the pervasiveness of ignorance, moral deviation and lack of learning. The Scholars Association was established under these circumstances, in order to contribute to the reformation and evolution of the miserable conditions of the Algerians; through the writings of its leaders, in different magazines and newspapers. Hence, this paper attempts to shed light on 'Essounna Ennabawia' -the first newspaper issued by the Association- through an analytical study of its subjects; focusing on the Association's different reformative roles; especially, the religious, political as well as the educational ones. "التربوي.
مذكرة ماستر تخصص دعوة واعلام
Keywords: الصحافة الإصلاحية, جمعية العلماء المسلمين الجزائريين, الطرق الصوفية, جريدة السنة النبوية.; Reformative journalism, the Algerian Muslim Scholars Association, the Sufist methods, Essounna Ennabawia Newspaper.